THE ANALYSIS OF HAMIT YERGALIYEV POETRY - Nagbdu, Kamarova (European Scientific Journal, ESJ, 2014)
A poet, having left an original trace in the history of Kazakh literature is Hamit Yergaliyev. A real poet is the voice and spirit of the nation. The poet who did not manage to become the voice of the nation is just poems redactor.